Feasibility of Assessing Prognostic Nutrition Index in Patients With Rectal Cancer Who Receive Preoperative Chemoradiotherapy. Issue 6 (7th January 2018) - Okugawa, Yoshinaga; Toiyama, Yuji; Oki, Satoshi; Ide, Shozo; Yamamoto, Akira; Ichikawa, Takashi; Kitajima, Takahito; Fujikawa, Hiroyuki; Yasuda, Hiromi; Saigusa, Susumu; Hiro, Junichiro; Yoshiyama, Shigeyuki; et al.
Abstract: Background: Malnutrition can adversely affect treatment responses and oncological outcomes in cancer patients. However, among patients with rectal cancer who undergo chemoradiotherapy (CRT), the significance of peri‐treatment nutrition assessment as a predictor of treatment response and outcome remains unclear. Objective: The aim of this study was to determine whether the Prognostic Nutrition Index (PNI) based on peri‐treatment serum can be used as a predictor of treatment response and outcome in patients with rectal cancer who undergo CRT. Design, Setting, and Patients: We analyzed 114 patients with rectal cancer who received preoperative CRT followed by total mesorectal excision at our institution. Results: Post‐CRT PNI was significantly lower than pre‐CRT PNI in rectal cancer patients. Although post‐CRT PNI did not significantly correlate with either overall survival or disease‐free survival, low pre‐CRT PNI was significantly associated with shorter overall survival and disease‐free survival in this population and was also an independent risk factor for ineffectiveness of long‐course preoperative CRT. Finally, low pre‐CRT PNIs were a stronger indicator of poor prognosis and early recurrence in patients with pathological lymph node metastasis (who generally need to receive postoperative chemotherapy), than in those with no pathological lymph node metastasis. Conclusion: Pretreatment PNI could be useful in evaluating and managing patients with rectal cancer who undergo CRT followed by curative resection.